Meningkatkan Hasil Belajar IPA Materi Tekanan Zat dengan Metode Penemuan Berbasis Lembar Kerja Siswa di Google Form pada Siswa Kelas VIII B SMP Negeri 2 Bangsalsari Jember - Anggraeni, Widoretno (Jurnal Simki Pedagogia, 2022)
The purpose of this study is to describe the increase in science learning outcomes of Substance Pressure material in online guided discovery learning through google meet through the use of student worksheets (LKS) on google form in class VIII B students of SMP Negeri 2 Bangsalsari Jember in the 2020-2021 academic year. semester 2. The research design used was classroom action research in two cycles. Each cycle consists of two meetings. Each cycle consists of planning, action, observation and reflection. Methods of data collection using the method of test, observation and documentation. The conclusion of this study is that the increase in science learning outcomes of Substance Pressure material in online guided discovery learning through google meet through the use of Student Worksheets (LKS) on google form in class VIII B students of SMP Negeri 2 Bangsalsari Jember in the 2020-2021 semester 2 academic year amounted to 27.39 with a percentage of 39.13%. The increase in student evaluation results from before the study the average value of students was 60.00 with the percentage of completeness 56.52% increased in the first cycle the average value of students was 74.57 with the percentage of completeness 73.91% and in the second cycle the average value the average student becomes 87.39 with a percentage of completeness of 95.65%.